TEKNIK RELAKSASI DALAM PROSES PERSALINAN : LITERATUR REVIEW - Ninik Azizah; Vivin Eka Rahmawati; Feny Vitiasari Dessy (Universitas Pesantren Tinggi Darul Ulum, 2022)
Pain during labor is basically caused by strong contractions during labor and it is a natural thing. Every woman has a different pain. Pain can occur due to other physical or physiological factors or it can also arise due to emotions or feelings in the woman. This is because of the negative suggestion factor that enters the subconscious mind, where the subconscious mind cannot distinguish between reality and imagination. The tension and fear felt by the mother cause pain during labor, thus slowing the delivery process. Labor pain can be controlled by 2 methods, namely pharmacological and non-pharmacological. Pharmacological pain relief methods are pain relief methods using chemical drugs, while non-pharmacological methods are natural pain relief methods without using chemical drugs by performing relaxation techniques, which are external actions that affect the individual's internal response. against pain. Pain management with relaxation measures include muscle relaxation, deep breathing, massage, meditation and behavior. This literature study uses the method of collecting data from systematic search/tracking studies of computerized databases (Pubmed, BMC, Cochrain review and Google Scholar), in the form of research journals and review articles. Breathing relaxation technique is a technique that is a pain relief technique that provides the greatest input because relaxation techniques in labor can prevent excessive errors after childbirth. The relaxation of breathing during labor can maintain the components of the sympathetic nervous system in a state of hemostasis so that there is no increase in blood supply, reduce anxiety and fear so that the mother can adapt to pain during labor. Keywords: Relaxation Techniques, Labor, Pain.